Histamine H3 Receptor Agonist Imetit Attenuated Isoproterenol Induced Renin Angiotensin System and Sympathetic Nervous System Overactivity in Myocardial Infarction of Rats - Hass, C.; Panda, B. P.; Khanam, R.; Najmi, A. K.; Akhtar, M. (Drug Research, 2016)
Background: Myocardial infarction is an alarming health issue, needs great attention. The present study investigated the role of histamine-H3 receptor (H3R) agonist imetit in relationship to sympathetic and renin angiotensin system in Wistar rats.Materials and Methods: Subcutaneous injection of isoproterenol (85 mg/kg) on last 2 consecutive days in per se group and 7 days treatment of different groups at 24 h interval induced myocardial infarction in Wistar rats. H3R agonist imetit (10 mg/kg), H3R antagonist thioperamide (5 mg/kg), losartan (10 mg/kg) were administered orally to evaluate imetit’s cardioprotective potential effect by measuring plasma cardiac antioxidant markers, angiotensin II, norepinephrine levels and histopathological analysis.Results: Isoproterenol significantly elevated the angiotensin II and norepinephrine levels in rat plasma. This study revealed that pre-treatment with imetit similar to losartan attenuated norepinephrine and angiotensin II levels whereas thioperamide showed its antagonistic effect by diminishing imetit’s effects. Furthermore, its protective effect was confirmed by restoration of cardiac antioxidant markers and histopathological improvement of myocardium integrity.Conclusion: This study confirm imetit’s cardioprotective potential and also reveals renin angiotensin system, sympathetic system and H3R correlation in isoproterenol induced toxicity in rats. However, molecular studies must be warranted to prove the role of H3R in myocardial infarction.
Keywords: imetit; isoproterenol; thioperamide; renin angiotensin system; norepinephrine